Synthesis and Application of Fe3O4/SiO2/TiO2 Nanocomposite as Photocatalyst in CO2 Indirect Reduction to Produce Methanol - Yudha Ramanda; Nuryono Nuryono; Eko Sri Kunarti (Indonesian Journal of Chemistry, 2019)
This study focuses on the synthesis and application of a Fe3O4/SiO2/TiO2 nanocomposite as a photocatalyst in CO2 indirect reduction. The synthesis was started by preparation of magnetite (Fe3O4) followed by silica (SiO2) coating and titania (TiO2) deposition. Magnetite was prepared by the sono-coprecipitation method, then the coating of SiO2 and deposition of TiO2 were performed by the sol-gel method under ultrasonic irradiation. All the material products were characterized by an X-ray diffractometer (XRD), Fourier-transform infrared spectrophotometer (FTIR), and transmission electron microscope (TEM). The final material product was also analyzed by a specular reflectance UV-Visible spectrometer (SR-UV-Vis) and the turbidimetry method. The product of the indirect reduction was analyzed by a gas chromatography-mass spectrometer (GC-MS). The XRD diffractograms and FTIR spectra confirmed the presence of Fe3O4, SiO2, and the anatase phase of TiO2. The TEM images revealed the presence of a core-shell nanocomposite with an average diameter of 19.22 ± 1.25 nm. The SR-UV-Vis spectrum was used to determine the band gap energy of the photocatalyst, with the result being 3.22 eV. Turbidimetry aimed to measure the magnetic recoverability of the final material, and the result was that it had better recoverability compared to a non-magnetic photocatalyst composite. The GC chromatogram of the indirect reduction product indicated four majorfractions; the MS spectra showed these to be methanol, formaldehyde, formic acid, and CO2. The GC-MS results revealed that CO2 indirect reduction achieved 73.91% conversion of CO2 and 55.01% selective to methanol.